KEKERASAN DISKURSIF ATAS NAMA “WAR ON TERRORISM” : BENTUK BARU PELANGGARAN HAM - Muhammad Zuhdan (Journal of Governance, 2016)
Abstract: This paper is about to see the discourse of the war on terrorism by using Foucaldian perspective. The thesis said that the discourse of "war on terrorism" is a product of hegemonic power and therefore has created a discursive violence that threaten human rights. The purpose is to provide an alternative approach in view of global and national discourse on the issue of the war against terrorism. Research result found interest fact that the fight against terrorism has threatened civil liberties and political freedom from violence discursive hegemony of power produced by the global and national levels. In addition this paper also offers how a modern government should do to counter terrorism based on Foucauldian approach.Keywords: Terrorism, Discourse, Hegemony, Discursive Violence, Human Rights